2012
DOI: 10.1186/1471-2334-12-208
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors for treatment delay in pulmonary tuberculosis in HIV-infected individuals: a nested case-control study

Abstract: BackgroundThe delay in initiating treatment for tuberculosis (TB) in HIV-infected individuals may lead to the development of a more severe form of the disease, with higher rates of morbidity, mortality and transmissibility. The aim of the present study was to estimate the time interval between the onset of symptoms and initiating treatment for TB in HIV-infected individuals, and to identify the factors associated to this delay.MethodsA nested case-control study was undertaken within a cohort of HIV-infected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…These clinical indicators likely increase the physician’s suspicion of severe TB and lead to empiric treatment. The factors found to be associated with both patient and health care delay in this study contrast with those from the study performed by Coimbra et al [ 15 ] where primarily clinical factors were found to be associated with greater total delay. Use of illicit drugs was the only social factor associated with later initiation of TB therapy in that study, but this finding was not replicated in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These clinical indicators likely increase the physician’s suspicion of severe TB and lead to empiric treatment. The factors found to be associated with both patient and health care delay in this study contrast with those from the study performed by Coimbra et al [ 15 ] where primarily clinical factors were found to be associated with greater total delay. Use of illicit drugs was the only social factor associated with later initiation of TB therapy in that study, but this finding was not replicated in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Use of illicit drugs was the only social factor associated with later initiation of TB therapy in that study, but this finding was not replicated in our study. Furthermore, based on the study done by Coimbra et al and others from different countries [ 15 , 25 ], we had expected to find that AFB smear and Xpert-MTB-RIF results were associated with health care delay. Interestingly, the results of microbiological testing did not impact delays in our study, and likely reflects the fact that empiric TB treatment is common in Brazil, as shown previously,[ 27 ] and may be more so in our sample as patients were seen by highly experienced infectious disease specialists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review also identified other sociodemographic and economic risk factors for patient delay, such as being older, lower education level, unmarried, being unemployed, absence of health insurance, and high cost of treatment and transportation to health facilities (Table 2). Urban residence [24,56,58] Widowed/di vorced/ separated/n ot married [67,75] Cost of health care incurred before diagnosis [46 ] Sub-urban residence [104 ] Widowed Unemployed [35,36,39] Cost of treatment/ transport to health facilities [86] Unemployed [101] Cost of treatment/ transport to health facilities [47] No health insurance [68,72,73,81] Cost of health care incurred before diagnosis [101 , 104] Behavioral Smoking [37] Recreational drug use [61] Smoking [77] Poor TB knowledge [98] Poor TB knowledge [46,104] Nonsmoking [99] Stigma[25, 40,57] Stigma [72,83] Stigma [ TB-HIV coinfection/HIV positive [30,88] No cough [66] No history of TB [97] Smear positive [78,99] No history of TB in the family [101] Chest pain [107] No history of TB [32,…”
Section: Patient Delaymentioning
confidence: 99%